Effect of different shadings on the environmental parameters - Bindu P K (Department of Land and Water Resources and Conservation Engineering, Kelappaji College of Agricultural Engineering and Technology, 2006)
Controlled environment agriculture in the form of shade houses, greenhouses, low tunnels and cloches are being practised at commercial levels in many countries. Among these, cultivation under shades is an easier method which is widely used for growing ornamental plants. Considering the scope of cultivating vegetables under shade nets, the thesis entitled ‘Effect of different shadings on the environmental parameters’ was undertaken. Four shade structures of size 6 m x 4 m x 2 m were constructed at the instructional farm, KCAET, Tavanur. The shade nets tested were green and black shade nests providing 50% and 75% shade respectively. The effect of shades on the environmental parameters such as temperature, relative humidity, solar radiation intensity and light intensity were studied. These parameters were compared with those in the open space. The temperature was reduced by the shade nets, but the reduction was only in the range of 0.5 to 4°C. The temperature under the black nets was higher than that under the green nets. The relative humidity was higher under the shade nets than in the open space. Also the RH under the green nets is higher compared to that under the black nets. The solar radiation intensity and the light intensity were reduced by the nets in varying ranges. The light intensity and solar radiation intensity under the black nets were very less compared to the green nets. The equations developed give a clear idea about the variation in environmental parameters under the shade nets. The growth of tomato was better in the open space than under the shades. The growth of and yield of amaranthus was better under the G50 shade net. The growth and yield of amaranthus grown in the open space was better compared to those obtained under the G75, B50 and B75 nets.